2021
DOI: 10.1039/d0ta10811a
|View full text |Cite
|
Sign up to set email alerts
|

When MOFs meet MXenes: superior ORR performance in both alkaline and acidic solutions

Abstract: The facilely synthesized Fe–N–C@Ti3C2Tx composite exhibited excellent ORR activity and extraordinary stability in both alkaline and acidic solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…To better understand the ORR activities, K-L plots were obtained at a few LSV rotating speeds, showing good linearity, suggesting a 4-electron transfer process. Very recently, Wang et al 195 introduced Fe-doped ZIF-8 as the Metal-Nitrogen-Carbon (M-N-C) material to be coupled with Ti 3 C 2 T x MXenes. The catalyst was produced through a separate pyrolysis strategy to ensure the high carbonization temperature needed for the high catalytic activity of Fe-N-C while avoiding MXene damage caused by a high pyrolysis temperature.…”
Section: Mxenes As Noble-free Catalyst Supportsmentioning
confidence: 99%
“…To better understand the ORR activities, K-L plots were obtained at a few LSV rotating speeds, showing good linearity, suggesting a 4-electron transfer process. Very recently, Wang et al 195 introduced Fe-doped ZIF-8 as the Metal-Nitrogen-Carbon (M-N-C) material to be coupled with Ti 3 C 2 T x MXenes. The catalyst was produced through a separate pyrolysis strategy to ensure the high carbonization temperature needed for the high catalytic activity of Fe-N-C while avoiding MXene damage caused by a high pyrolysis temperature.…”
Section: Mxenes As Noble-free Catalyst Supportsmentioning
confidence: 99%
“…Furthermore, from the structure and morphology characterizations of FeNC/ MXene, a thin FeNC coating was noticed on the MXene surface, forming a heterogeneous structured nanosheet elucidating admirable conductivity and electrocatalytic properties due to increased active sites on the substrate. Wang et al reported Fe-N-C@Ti 3 C 2 T x synthesized Fe doped ZIF-8 was carbonized to Fe-N-C. 108 The assynthesized catalyst achieved a limiting current density of 6.3 mA cm À2 with no attenuation even after 10 000 cycles in 0.1 M KOH. The electrocatalyst showed an outstanding stability in acidic medium (0.1 M HClO 4 ) even after 10 000 cycles only 11 mV attenuation was observed.…”
Section: Mxene As Elecrocatalyst For Orrmentioning
confidence: 99%
“…This is possibly a significant obstacle that results in a lack of studies on nonprecious ORR catalysts based on 2D MXenes, compared to other 2D materials such as graphene. In view of this, Wang et al [123] synthesized an Fe-N-C@Ti 3 C 2 T x catalyst, in which the Fe-N-C catalyst presynthesized from ZIF-8 (pyrolyzed at 1100 °C) was mixed with Ti 3 C 2 T x and further subjected to a low-temperature heat-treatment process (350 °C) to generate a high-surface-area ORR catalyst (Figure 11i). The layered Ti 3 C 2 T x was found to act as a substrate and effectively alleviated the agglomeration of Fe-N-C and enhanced the stability of the catalyst.…”
Section: Non-pt/mxene Catalysts For the Orrmentioning
confidence: 99%
“…m) LSV curves of MXene, Fe-N-C, Fe-N-C@MXene, and Pt/C in 0.1 m HClO 4 . Reproduced with permission [123]. Copyright 2021, Royal Society of Chemistry.…”
mentioning
confidence: 99%